Legal Politics of Zakat Empowerment in Indonesia (Dialectics of Islamic Fiqh Norms with Indonesian National Legal Policy) - Ahmad Hafidh (Universitas Sebelas Maret, 2025)
This paper intends to reconstruct the shari'ah of zakat by opening the dialectic of shari'ah norms (fiqh) of zakat by optimizing the role of the Indonesian state in its law enforcement. Ushuly (philosophical) reasoning, especially the Maqashid as-Shari'ah approach, has an important role in this study, so as to produce a political solution to sharia law that is more empowering for efforts to realize Islam rahmatan lil'alamin. This research uses qualitative method with the object of analysis is the views of scholars who are concerned with fiqh zakat. The ideas they express, whether in the form of seminar papers, books, opinions, or others, will be used as primary data. The data that has been collected will be analyzed using discourse analysis, which emphasizes the elements of text, context and discourse. In this research, it is found that the effort to empower the sharia of zakat as an instrument to realize the welfare of Muslims has undergone various evolutions in its implementation in various regions of Muslim countries through ijtihad efforts both istinbathy (interpretative) and tathbiqy (applicative), as well as historical and philosophical studies, while still paying attention to the principles and normative provisions of fiqh in order to achieve the purpose of institutionalizing Islamic law (al maqashid ash-syari'ah).